2017
DOI: 10.1111/adb.12510
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' behavioral and neural responses to e‐cigarette advertising

Abstract: Although adolescents are a group heavily targeted by the e-cigarette industry, research in cue-reactivity has not previously examined adolescents' behavioral and neural responses to e-cigarette advertising. This study addressed this gap through two experiments. In Experiment One, adult traditional cigarette smokers (n = 41) and non-smokers (n = 41) answered questions about e-cigarette and neutral advertising images. The 40 e-cigarette advertising images that most increased desire to use the product were matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…Whole-brain analyses revealed the activations induced by cue (smoking pictures vs. neutral picture) identified in previous nicotine addiction studies (Chen et al, 2018;Courtney, Ghahremani, London, & Ray, 2014;Yalachkov & Naumer, 2011), including left precuneus, rMFG and right inferior parietal lobule (Table 3) in the control state (see Supporting Information). Whole-brain analyses indicated the brain activation by cue (smoking pictures vs. neutral picture) was comprehensive during hypnotic state (Table 3).…”
Section: Effects Of Hypnotic Smoking Aversion Suggestion-fmri Datamentioning
confidence: 77%
“…Whole-brain analyses revealed the activations induced by cue (smoking pictures vs. neutral picture) identified in previous nicotine addiction studies (Chen et al, 2018;Courtney, Ghahremani, London, & Ray, 2014;Yalachkov & Naumer, 2011), including left precuneus, rMFG and right inferior parietal lobule (Table 3) in the control state (see Supporting Information). Whole-brain analyses indicated the brain activation by cue (smoking pictures vs. neutral picture) was comprehensive during hypnotic state (Table 3).…”
Section: Effects Of Hypnotic Smoking Aversion Suggestion-fmri Datamentioning
confidence: 77%
“…Nichols (2016) recently developed videos of e-cigarette use for cue-reactivity studies and pilot tested these in e-cigarette users (Nichols et al, 2016). In another fMRI study (Chen et al, 2017), adolescents with a range of regular cigarette use (never to daily) showed increased neural cue-reactivity as they viewed print e-cigarette advertisements, and reported increased craving to smoke regular cigarettes. For that study, e-cigarette advertisements were included if they had increased young adult smokers' desire to smoke regular cigarettes in an earlier behavioral study.…”
Section: Discussionmentioning
confidence: 99%
“…Soria Morillo et al [40], Yang et al [41], Cherubino et al [42], Soria Morillo et al [43], Vasiljević et al [44], Yang et al [45], Pilelienė and Grigaliūnaitė [36], Daugherty et al [46], Royo et al [47], Etzold et al [48], Chen et al [49], Casado-Aranda et al [50], Randolph and Pierquet [51], Nomura and Mitsukura [52], Ungureanu et al [53], Goyal and Singh [54], Oon et al [55], Singh et al [56].…”
Section: Promotionmentioning
confidence: 99%
“…[35], Gordon et al [59], Krampe et al [60], Hubert et al [25], Çakir et al [24], Holst and Henseler [61], Hsu and Cheng [62], Hoefer et al [27], Chen et al [49], Casado-Aranda et al [50], Wang et al [30], Jain et al [63], Wolfe et al [31], Bosshard et al [32], Fehse et al [33].…”
Section: Promotionmentioning
confidence: 99%